Neonatal survival analysis: the relationship between neonatal mortality and the number of antenatal care visits (2017 Indonesia Demographic and Health Survey) - Cahyanti, Betri; Ratrikaningtyas, Prima Dhewi; Wiratama, Bayu Satria (Universitas Gadjah Mada, 2024)
Purpose: In 2021, the number of under-five child deaths in Indonesia reached 27.566, with 28.158 (73,1%) of these being neonatal deaths. Indonesia implemented a minimum of four prenatal visits (K4) in 2019. The number of antenatal care (ANC) visits according to WHO standards has not been fully implemented nationwide in Indonesia. This study aims to analyze neonatal survival related to the number of ANC visits and neonatal death incidents based on the 2017 IDHS data. Methods: This study used a cross-sectional method with data from the 2017 IDHS. The sample included women of childbearing age (15-49 years) who had given birth within five years before the survey and had recorded ANC visits during their last pregnancy. Data analysis was performed using descriptive life-table and Kaplan-Meier Curve, bivariate analysis using Log Rank Test, and multivariate analysis using Cox Regression. Results: The study involved 13.826 women of childbearing age who were survey respondents. Univariate analysis showed that most respondents were at low risk during pregnancy (73.55%), belonged to the lowest wealth quintile (22.18%), and had a high education level (52.91%). Most babies were born with normal birth weight (92,89%) and were male (51,43%). The majority of ANC visits fell into the K6 category (47,59%). Kaplan-Meier survival analysis showed significant neonatal deaths within the first five days, with the survival probability dropping to 99,50% by the fifth day. Multivariate analysis identified maternal age, birth weight, baby's sex, and place of delivery as significant factors affecting neonatal mortality. Higher maternal age, lower birth weight, and male sex increased the risk of neonatal death, while delivering in a health facility was associated with higher neonatal mortality. Conclusion: The study found that ANC visits were significant in the K6 and K8 categories. However, when multivariate analysis was performed, the significance was lost when the birth weight variable was included. Most ANC visits were in the K6 category, which is Indonesia's standard for at least six antenatal visits. Maternal age, baby's sex, birth weight, and the number of babies significantly affected neonatal survival. The neonatal mortality rate was 6,4 per 1.000 live births.